Pristine and Alkylated MoS2 Nanosheets for Enhancement of Tribological Performance of Paraffin Grease under Boundary Lubrication Regime - Rawat S.S.; Harsha A.P.; Agarwal D.P.; Kumari S.; Khatri O.P. (My University, 2025)
In the present study, lubricating grease was developed with paraffin oil and 12-lithium hydroxy stearate metal soap as a thickening agent. MoS2 nanosheets were synthesized by hydrothermal method and functionalized with 1-octadecanethiol (i.e., MoS2-ODT). The MoS2 and MoS2-ODT nanosheets were dispersed in the grease with different concentrations to evaluate its tribological performance. Tribological results unveiled that the addition of MoS2 nanosheets in grease appreciably reduced the coefficient of friction and mean wear volume of tribo-interfaces as compared with pure grease. Energy dispersive spectroscopy (EDS) spectrum revealed the deposition of MoS2 on the worn surface and confirmed a thin tribo-film which protects steel tribo-pair against wear. © 2019 by ASME.